A new scheme for reducing pressure drop and thermal resistance simultaneously in microchannel heat sinks with wavy porous fins. (August 2017) - Lu, Gui; Zhao, Jun; Lin, Lin; Wang, Xiao-Dong; Yan, Wei-Mon
Highlights: New way to reduce pressure drop and thermal resistance in microchannel heat sink. Mechanisms on reduction of pressure drop and thermal resistance are revealed. Various designs are used to examine the effectiveness of new concept heat sinks. Abstract: A new design of wavy microchannel heat sink with porous fins is proposed to reduce simultaneously pressure drop and thermal resistance. A three-dimensional solid-fluid conjugate model with considering heat transfer and flow in porous media is adopted to validate the effectiveness of the new design. The results show that the wavy microchannel heat sink with porous fins reduce simultaneously pressure drop and thermal resistance compared with conventional wavy microchannel heat sinks with solid fins. The marked pressure drop reduction in the wavy microchannel with porous fins comes from the combination of permeation effect and the slip effect of the coolant fluids. The improvement of heat transfer performance is attributed to the combinative effect of the enhanced coolant mixing by Dean vortices, the prolonged flow route by increasing equivalent channel length, and the forced permeation by jet-like impingement. The new concept is also examined for various microchannel heat sink designs with different wavy amplitude, wavelength, channel width and channel height, which indicates the wide range of applicability of the new microchannel concept.